ANALISIS PENGGUNAAN APLIKASI MOBILE DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Susilawati, Reni; Andriansah, Zjulpi; Erhassa, Shalicha Nafilata; Fitri, Nanda Inka; Mustofa, Ihsan (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
Mobile applications are used in Islamic Religious Education (PAI) learning along with technological advances. The purpose of this study was to study the use of mobile applications in PAI learning at SMPN 1 Buay Bahuga. This study was conducted using a qualitative descriptive method. Data collection through observation, interviews, and documentation with PAI students' and teachers' research subjects. Data analysis uses the Miles and Huberman analysis model which includes data reduction, data presentation, conclusions/verification. To obtain valid data, triangulation of sources and methods is used. The results showed that the use of mobile applications such as digital Al-Qur'an applications, e-learning, and other interactive media improved students' understanding of PAI material. However, there are several obstacles to implementing it, such as limited internet access and some students do not have sufficient digital skills. This study found that mobile applications can help improve the quality of PAI learning if supported by adequate infrastructure and digital literacy.